Integrating CEMDAP and MATSIM to Increase the Transferability of Transport Demand Models. Issue 1 (January 2015) - Ziemke, Dominik; Nagel, Kai; Bhat, Chandra
An activity-based approach to transport demand modeling is considered the most behaviorally sound procedure to assess the effects of transport policies. This paper investigates whether it is possible to transfer an estimated model for activity generation from elsewhere (the estimation context) and use local area (application context) traffic counts to develop a local area activity-based transport demand representation. Here, the estimation context is the Los Angeles, California, area, and the application context is Berlin. Results in this paper suggest that such a transfer approach is feasible, according to a comparison with a Berlin travel survey. Additional studies need to be undertaken to examine the stability of the results obtained in this paper.